Educação financeira: praticando o consumo consciente no ensino fundamental - Carrara, Antonio Marco Campos (2017)
This work is part of a Master's Degree research on Financial Education in the 9th year of Middle School. A group of thirty five students between the ages of fourteen and fifteen from a public school located in the Baixada Fluminense participated in this research. The main objective of this work is to provide the students with information, providing financial problem situations based on explanations about the subject, using technological means so that they can reflect on a balanced financial life and have possession of tools to be used at the time of decision making. The research took place during the years of 2015 and 2016 and was guided by the theoretical and methodological assumptions of Didactic Engineering, which was fundamental for the execution of this qualitative research. During its four phases preliminary, a priori analysis, experimentation and a posteriori analysis and validation, the students participated in eight weekly meetings of 100 minutes each, when, at the opportunity, they discussed subjects from the history of money to the use of checks and credit cards, loans, financing, savings, taxes and family budget. The educational product, resulting from the research, culminated in the creation of an website that provides videos, texts and applications to educators and young people about the subject, hoping that the target audience, composed of teachers and students, can each guide themselves, ask questions, multiply the knowledge acquired and help the people around them, favoring school and life learning.